Numerical investigation on the effects of nozzle geometry on the performance of a pulse detonation engine - Amin, M. Rahul (Strojniški vestnik, 2005)
A numerical study is presented on the effects of various nozzle geometries andoperating conditions on the performance of a Pulse Detonation Engine (PDE).An unsteady numerical simulation model, which is second order accurate in space and first order accurate in time, using an automated Java based computational fluid dynamics (CFD) software is presented. One- and two-dimensional transient CFD models were employed in a systematic manner to study the propulsive performance characteristics of the PDE under different operating conditions. Preliminary studies of the effects of nozzle geometry on the performance characteristics of a generic PDE are presented. The results indicate that an expanding nozzle, capable of adapting with the cycle time and the ambient pressure, is very suitable for optimizing the PDE performance. Addition of a straight, diverging or converging nozzle improves the performance. However, it is observed that there is an optimum value of theexit area of a divergent nozzle for performance improvement. At low ambientpressure addition of a nozzle increases the specific impulse of the PDEtube. It is also seen that a diverging nozzle is more effective than a converging-diverging nozzle at low ambient pressure. The study indicates that increased volume of the reacting fuel mixture has a negative effect on the PDEperformance. The results show that a 25% reduction of the reacting fuel mixture leads to approximately 18% increase in the value of the specific impulse.
Keywords: motorji pulzni; geometrije šob; modeli simulacijski; metode numerične; motorji; geometrija; šobe; izgorevanje; simulacije; numerične metode